STRATEGI SYNERGETIC TEACHING UNTUK MENINGKATKAN KETERAMPILAN MEMBACA MAHASISWA SEMESTER TIGA STAIN PAREPARE - Mujahidah, Mujahidah; Nanning, Hj. Nanning; Selle, Amzah (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2015)
This study was born from an anxiety researcher to observe the phenomenon of learning that takes place in the classroom. Most teachers are less variable in applying the teaching method or strategy. By him that researchers believe that the strategy of synergetic teaching is a viable alternative to be applied in the classroom. This research is a classroom action research (Classroom Action Research). The purpose of this study was to assess the success of a learning strategy or what is known in this research is synergetic teaching strategies in reading course. Besides this research also focus on the implementation of teaching strategies in the classroom especially synergetic pda reading half of the three subjects. After doing some research, the researchers found, there was a signiï¬cant increase to the skill of reading (reading) students after applying synergetic teaching strategy. Furthermore, the application of synergetic teaching strategies in reading subjects also received a positive response from the students (contributor). It is characterized by three indicators, namely liveliness asked, enthusiastic attitude of students, and analysis of the results of student readings. All three of these indicators also improved quite well after applying the strategy of synergetic teaching. By it, the researchers concluded that the strategy of synergetic recommended teaching ought to be applied in the classroom, especially those not on course reading, but also other subjects.